TARI LANGKAH MAMBUNGA: STILISASI GERAK KUNTAU - Safana Muzdalifah; Andi Wijaya; Dewi Rukmini Sulistyawati (STKIP PGRI BANJARMASIN, 2021)
Kuntau as a traditional martial art located in Hulu Sungai Selatan is one of the cultures that has noble values. The creation of the Step Mambunga dance was worked on by the Karamunting studio (2018) with inspiration from Kuntau. The purpose of this study is to describe the stylization of the kuntau movement in the Step Mambunga dance and describe the form of its presentation. This study uses a descriptive qualitative approach with data collection techniques interview, observation, literature study, and documentation. The data obtained then went through the stages of analysis and drawing conclusions. The results of this study are that the stylization is carried out based on volume, dimensions, and level, there are 4 kuntau moves and 8 various movements that have been smoothed and arranged into the Mambunga Step dance. This is set in the storyline which is divided into 3 scenes about young people who are learning Kuntau to batamat kuntau as local culture. There were 13 dancers consisting of 10 women and 3 men. The floor designs formed are 17 designs with musical accompaniment that is identical to the sarunai on kuntau but combined with several other musical instruments. Sticks, nyiru, parapins, lawing sakiping (symbol of an arena) and cloth are used as dance properties. The lighting functions as lighting and strengthening the atmosphere in each scene, while the venue for the performance is a procenium stage with a fairly wide size criteria. Keywords: Dance, Langkah Mambunga,Stylization, Kuntau